2021
DOI: 10.3390/molecules26164835
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Pesticides as an Alternative to Pest Management and Sustainable Agricultural Production: Prospects, Applications and Challenges

Abstract: Pests and diseases are responsible for most of the losses related to agricultural crops, either in the field or in storage. Moreover, due to indiscriminate use of synthetic pesticides over the years, several issues have come along, such as pest resistance and contamination of important planet sources, such as water, air and soil. Therefore, in order to improve efficiency of crop production and reduce food crisis in a sustainable manner, while preserving consumer’s health, plant-derived pesticides may be a gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(117 citation statements)
references
References 118 publications
1
107
0
9
Order By: Relevance
“…Chemical control measures damaging virus epidemics in cultivated plants faced with increasing concerns over sustainability, human health, environment protection and social issues [ 22 ]: pesticides are recognized as a central responsible factor for the observed terrestrial biodiversity declines [ 23 ], as they are found as contaminants in soil, air, water, and non-targeted organisms [ 24 ]. Plants extracts and pure compounds have been described as potential tools to manage different crop pests and weeds, due to easily available sources, low cost, biodegradability, varied modes of action, and low toxicity to non-targeted organisms [ 25 , 26 , 27 , 28 , 29 ]. Activity of plant compounds against phyto-viruses has been reported [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical control measures damaging virus epidemics in cultivated plants faced with increasing concerns over sustainability, human health, environment protection and social issues [ 22 ]: pesticides are recognized as a central responsible factor for the observed terrestrial biodiversity declines [ 23 ], as they are found as contaminants in soil, air, water, and non-targeted organisms [ 24 ]. Plants extracts and pure compounds have been described as potential tools to manage different crop pests and weeds, due to easily available sources, low cost, biodegradability, varied modes of action, and low toxicity to non-targeted organisms [ 25 , 26 , 27 , 28 , 29 ]. Activity of plant compounds against phyto-viruses has been reported [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The isolated compound may act as a lead compound or prototype for the synthesis or semi synthesis of pesticide derivatives, which may result in more effective and safer products. However, it should be noted that the isolated compound may promote no activity at all because EO is more effective due to the synergic effect of compound mixture [47].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of a phytochemical can change significantly depending on the plant species, plant part and its age, polarity of solvents used during extraction procedures and mosquito species [104]. Phytochemicals show their effects through targeting important cell components and affecting insect physiology in different ways; via inhibition of AChE and GABA-gated chloride channel activity, disruption of sodium-potassium ion exchange and nerve cell membrane action, blocking calcium channels, and activation of nicotinic acetylcholine receptors and octopamine receptors [105]. Moreover, phytochemicals can cause cellular destruction of epithelial cells in the midgut of mosquitoes and affect metamorphosis [106,107].…”
Section: Plant-based Bioinsecticidesmentioning
confidence: 99%